Viewing the leadership narrative through alternate lenses: An autoethnographic investigation - Ken W. Parry (Management Revue, 2008)
This conceptual-theoretical article revisits the work of Parry and Hansen on the nature of the organizational story as leadership. The present article is written in the autoethnographic style. The original narrative work is re-examined through the lenses of autoethnography, narrative theory, metaphor/discourse, critical realism and conventional quantitative research. The insights provided by this methodological triangulation are examined. The conclusion is that organizational stories will reflect leadership if they are plausible to the intended audience, give all organizational members an empowered part in the story, have a moral to the story, and have a happy ending. The overarching theme that is proposed is of leadership as the generation of individual hope for a better existence.
Keywords: 650; organizational story; leadership; autoethnography; critical realism; metaphor